Hybrid QKD Protocol Outperforming Both DV- and CV-QKD Protocols - Ivan B. Djordjevic (IEEE Photonics Journal)
To overcome the limitations of both discrete variable (DV) and continuous variable (CV) QKD protocols, in this paper, a hybrid QKD protocol is proposed. In the proposed hybrid QKD protocol, Alice simultaneously performs discrete modulation (DM)-based encoding for CV-QKD subsystem and time-phase encoding for DV-QKD on a transmitter side and transmits such hybrid encoded pulse with optimized average number of photons per pulse. On receiver side, Bob employs a 1:2 optical space switch to select either DV-QKD receiver or CV-QKD receiver with the optimized probability of selection. Other compatible CV-QKD and DV-QKD protocols can also be used in hybrid QKD. Bob further performs the classical postprocessing applied to both subsystems so that resulting joint secure key is derived from both subsystems. The proposed hybrid QKD protocol significantly outperforms previously introduced both Gaussian modulation (GM)- and DM-based CV-QKD protocols as well as DV-QKD protocols in terms of both secret-key rate and achievable transmission distance.